Peran Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Karyawan Fazia Beauty Metro - Denny Kurniawan; Sastya Putri (Jaanur Elbarik Indonesia, 2026)
This research was conducted ad Fazia Beauty Metro. The aim of this study was to examine how Human Resource Management (HRM) plays a role in improving employe performance. This qualitative descriptive research presents data systematically, factually, and accurately. This purpose of this study is to descive and document the events and phenomena occurring in the field. To collect data, observation, interviews, and documentation were used, and the researcher employed source triangulation to verify the accuracy of the data and draw conclusions. The research results indicate that the recruitment process, job training, and appreciation are some of the human resource management strategis used by Fazia Beauty Metro to improve employe performance. Conversely, HR management at Fazia Beauty Metro faces challenges. This challenge comes from both internal company sources and external sources.